Perception about Artificial Intelligence in Medical Education - Shaima Sultana Memon, Saima Murad, Syed Abdul Rauf Shah, Zafar Iqbal, Rehana Saeed, Juweria Abid, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: There is increasing interest regarding the role of artificial intelligence and machine learning in medical education and the studies revealed about existing gap in knowledge and application of artificial intelligence. The aim of current study was to find out the perception of medical faculty members about artificial intelligence in medical education and the level of awareness regarding the basic concepts of artificial intelligence. Methods: A qualitative exploratory approach was conducted. A self-designed, self-explanatory questionnaire was used. The questionnaire was disseminated using google form. The link of the questionnaire was emailed to the chosen faculty members and appointment for the telephonic interview was taken. On the given date and time, they were called for the telephonic interviews and the calls were recorded. After recording all the calls, the data was transcribed from each recorded phone call. After transcription the data was coded and themes were identified for final analysis. Results: Majority of participants explained artificial intelligence as an advance data calculator while some were not aware of practical applications of artificial intelligence in the field of medicine. Majority of participants recommended that medical curriculum should be revised with incorporation of basic concepts of artificial intelligence based-medical education and computer education along with it. Workshops and seminars, CME on artificial intelligence to be conducted as a part of regular faculty development programs. Many participants predicted that healthcare professionals will be replaced with the artificial intelligence based computer programs for the diagnosis of diseases in the future. Conclusion: Current study made an important observation that there was the lack of conceptual knowledge about artificial intelligence and its applications, it could be due to the fact that the healthcare providers are more focused towards their own subject specialties, that leaves them with less time in exploring the computer based technologies. Keywords: Artificial intelligence, Healthcare system, Medical education